2016
DOI: 10.1371/journal.pone.0168210
|View full text |Cite
|
Sign up to set email alerts
|

(GT)n Repeat Polymorphism in Heme Oxygenase-1 (HO-1) Correlates with Clinical Outcome after Myeloablative or Nonmyeloablative Allogeneic Hematopoietic Cell Transplantation

Abstract: Allogeneic hematopoietic cell transplantation (HCT) is a treatment for various hematologic diseases where efficacy of treatment is in part based on the graft versus tumour (GVT) activity of cells in the transplant. The cytoprotective enzyme heme oxygenase-1 (HO-1) is a rate-limiting enzyme in heme degradation and it has been shown to exert anti-inflammatory functions. In humans a (GT)n repeat polymorphism regulates the expression of HO-1. We conducted fragment length analyses of the (GT)n repeat in the promoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…It has been proposed that a higher HO-1 expression level prevents the progression of GVHD and acts prophylactically on sinusoid obstruction syndrome (SOS), while promoting relapse [39][40][41]. Although the results of this study suggest that the higher expression of HO-1 is associated with favorable survival outcomes after allo-HSCT, the higher expression of HO-1 has not been shown to affect the risk of disease relapse or the development of GVHD.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…It has been proposed that a higher HO-1 expression level prevents the progression of GVHD and acts prophylactically on sinusoid obstruction syndrome (SOS), while promoting relapse [39][40][41]. Although the results of this study suggest that the higher expression of HO-1 is associated with favorable survival outcomes after allo-HSCT, the higher expression of HO-1 has not been shown to affect the risk of disease relapse or the development of GVHD.…”
Section: Discussioncontrasting
confidence: 57%
“…Namely, HO-1 derived from the vascular endothelium may be involved in the suppression of GVL effects and GVHD development, whereas HO-1 derived from donor blood cells may be mainly responsible for its anti-inflammatory and cytoprotective effects, leading to the prevention of organ damage. However, contrary to this hypothesis, a recent report from Denmark [39] showed that higher HO-1 expression derived from the donor may be associated with a higher risk of relapse after allo-HSCT, based on an investigation of the (GT) n repeat in the promotor region of donors and recipients receiving allo-HSCT. Differences between the Japanese and Danish ethnic groups might account for the role of HO-1 in the induction of the GVL effect.…”
Section: Discussionmentioning
confidence: 92%
“…(2008) might be due to increased susceptibility to infections and disease relapse rather than GVHD ( 23 , 27 29 , 52 ). Another study observed a higher incidence of grade III/IV acute GVHD in the donor L/L genotype group in the non MAC regimens cohort but not in the MAC regimens cohort ( 53 ). In the MAC cohort, they also found a significantly higher relapse incidence in the donor S/S genotype group, but no difference in overall survival.…”
Section: Discussionmentioning
confidence: 98%
“…The mitogen active protein kinase (MAPK) pathway corresponds to a well-known signaling pathway leading to HO-1 expression, principally in response to hypoxia [ 21 ]. Furthermore, the length of a (GT)n dinucleotide repeat in the promoter region of HO-1 exhibits variable transcription capacity, correlating a long length with a poor transcription while a short length is associated with an increased HO-1 transcription [ 22 ].…”
Section: Regulation Of the Ho Activitymentioning
confidence: 99%
“…Furthermore, in knockout mice, the absence of HO-1 correlated with a Th1 shift in cytokine responses and a predominantly pro-inflammatory state [ 88 ]. Moreover, HO-1 induction is also associated with a successful allogenic hematopoietic cell transplantation for acute leukemia [ 22 , 89 ].…”
Section: Therapeutic Implications Of Ho Inhibitorsmentioning
confidence: 99%